Perspektif Komunikasi Ritual dalam Tradisi Kelahiran Anak pada Masyarakat Bugis di Kelurahan Talaka Kecamatan Ma’rang Kabupaten Pangkajene dan Kepulauan - Nurfadilah , Nurfadilah; Majid, Abd; Muliadi , Muliadi (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
The purpose of this study was to examine the perspective and meaning in the tradition of child birth in the Bugis community in Talaka Village, Pangkep Regency. The research method used is a qualitative research method with as many as 4 (four) informants, namely traditional birth attendants and the general public who use the services of traditional birth attendants with data collection techniques carried out in two ways, namely, primary data and secondary data. The method of data collection by conducting observations, interviews, documentation. The results show that ritual communication is always identified with habits or routines, understands rituals as a hereditary action that also contains transcendental values, rituals have a relationship with voluntary performances that are carried out from generation to generation based on habits. As a sociocultural unit, the community has long had a set of traditional ceremonies. Until now they still maintain the values contained in the traditional ceremony. Considering that these ceremonies have spiritual and social functions, psychologically it can create peace of mind, feel safe and calm that can be felt in the heart.